2004
DOI: 10.1021/jf048537+
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation Chemistry of the Insecticide Phosmet in Lipid Models and in the Presence of Wool Wax, Employing a 15N-Labeled Compound

Abstract: The organophosphorus insecticide phosmet is commonly used for plant protection as well as against pests on animals. Phosmet features numerous degradation pathways induced by UV irradiation. In this study, we focused on the reaction possibilities of phosmet in the presence of lipophilic substances with olefinic structure elements, as they are frequently found in animal fur lipids, especially in wool wax. In the first step, simple models were employed to characterize the structural types of formed photoaddition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Although extensive data exist on photolysis of agrochemicals in water and soil media, a very limited number of studies have assessed their photoreactivity at the surface of plant leaf models such as cuticular waxes. Using model systems such as isolated cuticles or thin paraffinic wax films, it was reported that the photolysis rates of some pesticides at the surface of plant waxes can be significantly faster or slower compared with corresponding photolysis half-lives in water and soil. ,, It has also been shown that some formulation agents, particularly surfactants and photosensitizing herbicides, can promote photodegradation of active ingredients when used in a mixture . These studies have highlighted the need for systematic and realistic assessment of the photodegradation of agrochemicals on the surface of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although extensive data exist on photolysis of agrochemicals in water and soil media, a very limited number of studies have assessed their photoreactivity at the surface of plant leaf models such as cuticular waxes. Using model systems such as isolated cuticles or thin paraffinic wax films, it was reported that the photolysis rates of some pesticides at the surface of plant waxes can be significantly faster or slower compared with corresponding photolysis half-lives in water and soil. ,, It has also been shown that some formulation agents, particularly surfactants and photosensitizing herbicides, can promote photodegradation of active ingredients when used in a mixture . These studies have highlighted the need for systematic and realistic assessment of the photodegradation of agrochemicals on the surface of plants.…”
Section: Introductionmentioning
confidence: 99%
“…As a worldwide-used insecticide, phosmet [ O , O -dimethyl S -(phthalimidomethyl) phosphorodithioate (Figure )] is a nonsystemic organophosphate insecticide belonging to a subclass of dithiophosphates. , Phosmet is mainly applied on plants and productive livestock for control of pests that would induce the reduction of quantity and quality. , The principal toxic effect due to exposure to phosmet is related to irreversible inhibition of the acetylcholinesterase enzyme, which could cause acute effects on humans. , Besides, it was reported that exposure to phosmet could affect human placental phosphoinositides metabolism and inhibit neurite outgrowth through the synergistic effect with other insecticides . In recent years, several studies indicated that long-term exposure to low levels of phosmet might lead to impaired neurobehavioral performance and the risk of astrocytoma in offspring .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the studies on phosmet have to date mainly concentrated on photolysis, hydrolysis, and microbial degradation. Phosmet is of low persistence in the soil environment with a representative half-life of about 19 days, and it can be broken down through hydrolysis and microbial action in the soil environment. , In the aqueous environment, it is subject to hydrolysis under neutral and alkaline conditions and to a much lesser extent under acidic conditions. , Many efforts have been made to reveal the photoproducts and mechanism of the photodegradation of phosmet as photolysis plays an important role in the transformation and degradation processes of pesticides in the environment. ,,,, Tanabe et al identified N -methylphthalimide and N -methoxymethylphthalimide as the main photolytic products of phosmet in diethyl ether . Sinderhauf and Schwack identified phthalimide, N -hydroxymethylphthalimide, and N -methoxymethylphthalimide as the photoproducts of phosmet in model solvents (cyclohexane, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations